Acute effects of static and dynamic stretching on preparation and neuromuscular activation for resistance exercise practice: an integrative review (Research, Society and Development, 2022)
Strength and flexibility help people achieve healthy levels of physical fitness and functional autonomy and play key roles in reducing sports injuries and improving skills (Li et al., Mahesh, Joladarashi, and Kulkarni). In this sense, the objective of this work is to verify, in the light of the current literature, the acute effects of static and dynamic stretching on the preparation and neuromuscular activation for the practice of resistance exercise. This work is an integrative review, studies were searched in the database: National Library of Medicine of the United States - PUBMED, WEB OF SCIENCE and SCIENCE DIRECT, from June to November 2022. Most of the studies consulted show that does occur, improvement in ROM both soon after AE and AD, however, with damage to strength peaks, which in conclusion is inappropriate as part of the preparation before the practice of TR. On the other hand, three of the consulted studies reported that there is no such damage to the manifestations of muscle strength when using both AE and AD.